Green communication and networking : Second International Conference, GreeNets 2012, Gandia, Spain, October 25-26, 2012, Revised Selected Papers - Rodrigues, Joel J. P. C.; Mauri, Jaime Lloret (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2013)
This book constitutes the thoroughly refereed proceedings of the Second International Conference, GreeNets 2012, held in Gaudia, Spain, in October 2012. The 11 revised full papers presented were carefully selected and reviewed. These papers represent 23.68% of the submissions and cover topics such as communications and networking, energy-efficient network architecture and protocols, systems and technologies, and energy-efficient management.